Superman, the Golden Age volume one - Siegel, Jerry, 1914-1996 (DC Comics, 2016)
"When the last son of Krypton was sent to Earth, one of the greatest legends of all time was born. This edition collects some of the earliest tales of Superman as they were first published. Written and drawn by his creators, Jerry Siegel and Joe Shuster, included here are the original first appearances of Lois Lane, Jimmy Olsen, and Superman's alter ego Clark Kent, as well as the Man of Steel's first use of his x-ray vision. Collects Action Comics #1-12, Superman #1-4 and World's Fair Comics #1"--